2005
DOI: 10.1002/eqe.461
|View full text |Cite
|
Sign up to set email alerts
|

On tuned mass dampers for reducing the seismic response of structures

Abstract: SUMMARYThis paper presents an energy-based theoretical model for a two degree-of-freedom mechanical system. After a general formulation in Appendix A, the model is specialized to study tuned mass dampers as a means to substantially increase modal damping in order to induce a consequential decrease of the seismic response of the structures thus provided. Although approximate since it neglects coupling due to damping, it is shown that the model yields a ÿrst-order approximation to the exact frequencies, providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
67
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 3 publications
5
67
1
7
Order By: Relevance
“…In the mainstream literature, the seismic input has been usually assumed in post‐tuning numerical trials, in order to investigate the effectiveness of a specific tuning theory within the seismic context. Miranda proposed a numerical tuning procedure based on an energy‐based model, whose results confirmed those obtained by Sadek et al . ; Marano et al .…”
Section: Introductionsupporting
confidence: 76%
“…In the mainstream literature, the seismic input has been usually assumed in post‐tuning numerical trials, in order to investigate the effectiveness of a specific tuning theory within the seismic context. Miranda proposed a numerical tuning procedure based on an energy‐based model, whose results confirmed those obtained by Sadek et al . ; Marano et al .…”
Section: Introductionsupporting
confidence: 76%
“…Even though all of the earlier mentioned studies have widely demonstrated that the use of TMD on inelastic structures enhances the ability of the system to reduce plastic energy dissipation [8][9][10][11], most of these researches were based on deterministic analysis and made use of a few number of earthquake time-histories for their numerical simulations, and a larger number of records should be considered in order to draw out more general conclusions. Moreover, in the same studies, the optimization problem of the design parameters of TMDs on inelastic structures and the sensitivity analysis to some of the main important hysteretic mechanical characteristics have never been treated.…”
Section: Introductionmentioning
confidence: 98%
“…The effectiveness of TMDs in reducing structural response from the point of view of energy was studied by Wong and Chee [9], which investigated the energy balance of the TMD-primary structure system. Also Miranda [10] performed a study on SDOF structures with TMDs. He found that the equivalent damping in the equivalent elastic structure is increased and therefore damping energy dissipation is also increased accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration‐suppression systems have been used for decades to protect structures against potential damage caused by seismic loads. In addition to already‐classical devices, such as viscous dampers (VD)() or tuned mass dampers,() novel devices, such as tuned mass‐damper inerters (TMDI) or tuned inerter dampers (TID) have been proposed to address this problem in recent years. These devices incorporate inerters, devices that are able to generate forces proportional to the relative accelerations between their nodes.…”
Section: Introductionmentioning
confidence: 99%